A case-study on profiling Italian consumers of animal-friendly foods. Issue 2 (2nd April 2016) - Di Pasquale, Jorgelina; Nannoni, Eleonora; Adinolfi, Felice; Del Duca, Isabella; Capitanio, Fabian; Sardi, Luca; Vitali, Marika; Martelli, Giovanna
Abstract: Our research is based on 335 consumer interviews, conducted near and within supermarkets and hypermarkets in Bologna (North-Italy) and in its province. A multiple correspondence analysis followed by a cluster analysis were carried out in order to profile consumers based on their knowledge of farming conditions, their knowledge of "animal friendly" products and their willingness to pay for them. The analysis identified four groups of consumers (clusters). Groups were called: (1) "sensible and aware consumers" (36%); (2) "unconcerned consumers" (33%); (3) "the insiders" (6%) and (4) "uninvolved consumers" (25%). The first group represents an important market segment for "animal friendly" products. However, a diffused lack of knowledge was observed towards the issues of animal welfare and animal protection. These results urge a reflection on the needs and the risks that may underlie the creation of a shared European label for animal-friendly foods in order to minimize the risk of a failure of the certification scheme.